The effects of a passive exoskeleton on muscle activity, discomfort and endurance time in forward bending work. (May 2016) - Bosch, Tim; van Eck, Jennifer; Knitel, Karlijn; de Looze, Michiel
Abstract: Exoskeletons may form a new strategy to reduce the risk of developing low back pain in stressful jobs. In the present study we examined the potential of a so-called passive exoskeleton on muscle activity, discomfort and endurance time in prolonged forward-bended working postures. Eighteen subjects performed two tasks: a simulated assembly task with the trunk in a forward-bended position and static holding of the same trunk position without further activity. We measured the electromyography for muscles in the back, abdomen and legs. We also measured the perceived local discomfort. In the static holding task we determined the endurance, defined as the time that people could continue without passing a specified discomfort threshold. In the assembly task we found lower muscle activity (by 35–38%) and lower discomfort in the low back when wearing the exoskeleton. Additionally, the hip extensor activity was reduced. The exoskeleton led to more discomfort in the chest region. In the task of static holding, we observed that exoskeleton use led to an increase in endurance time from 3.2 to 9.7 min, on average. The results illustrate the good potential of this passive exoskeleton to reduce the internal muscle forces and (reactive) spinal forces in the lumbar region. However, the adoption of an over-extended knee position might be, among others, one of the concerns when using the exoskeleton. Highlights: A passive exoskeleton lowers back muscle activity by 35–38% during assembly work. The endurance time was found to be almost three times longer when using this system. The system reduced discomfort in the back but resulted in more discomfort in the chest.